2007
DOI: 10.1007/s11255-007-9179-9
|View full text |Cite
|
Sign up to set email alerts
|

The investıgatıon of GSTT1, GSTM1 and SOD polymorphism in bladder cancer patıents

Abstract: Glutathione S transferases (GSTT1, GSTM1, GSTP1) are enzymes that activate the detoxification of endogenous and exogenous agents. The genetic polymorphism in these genes may change the response of individuals to environmental toxicants. The genetic polymorphisms of GSTT1, GSTM1, GSTP1 have been studied extensively in the determination of individual cancer risks. Some studies showed a strong relationship between polymorphism of GSTs and superoxidedismutase enzymes. Using the polymerase chain reaction (PCR) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
2
14
1
1
Order By: Relevance
“…Similarly, means of all tissue parameters measured were also statistically similar between the patients of control group with no documented cancer as independent from the presence of urinary infection. Several studies have concluded that increased TBARs level and decreased SOD, GSH-Px, and XO in infectious tumor tissue as contrary to our results (29,30,34).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, means of all tissue parameters measured were also statistically similar between the patients of control group with no documented cancer as independent from the presence of urinary infection. Several studies have concluded that increased TBARs level and decreased SOD, GSH-Px, and XO in infectious tumor tissue as contrary to our results (29,30,34).…”
Section: Discussioncontrasting
confidence: 99%
“…This study indicated that cancer tissue samples could be used as a test material to study oxidative stress by evaluating their XO enzyme activities (12). To our knowledge, the results of our study supported with the results obtained before by the other researchers (26,30). In animals study the repercussions on the antioxidant and lipid peroxide status of the growth of human malignant tumors xenografted into athymic mice was evaluated (27).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We did not observe an increased BC risk between null and wild types of GSTM1 gene. In previous studies, while some investigators reported an association between null genotype and overall BC risk (Toruner et al, 2001;Cengiz et al, 2007), another did not (Altayli et al, 2009). GSTT1 null genotype was reported to be associated with increased BC risk among smokers in Turkish population (Altayli et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Lightfoot et al also reported decreased incidence of non-Hodgkin's lymphoma in homozygotes for the SOD2 16Ala allele in the UK population (27). Additionally, studies on bladder cancer were unable to indicate a positive correlation between polymorphisms within SOD gene and the occurrence of this form of cancer (32,33). According to the results presented by our study and other investigators, it may be concluded that the correlation between SOD2 polymorphisms is dependent on the kinds of cancers, for example, prostate and breast cancers appear to a have positive correlation, while, bladder and hematological malignancies, like lymphoproliferative disorders, are not associated with the polymorphisms of SOD2.…”
Section: Discussionmentioning
confidence: 99%